Novel Compound Heterozygous Pathogenic Mutations of SLC5A5 in a Chinese Patient With Congenital Hypothyroidism - Zhang, Cao-Xu; Zhang, Jun-Xiu; Yang, Liu; Zhang, Chang-Run; Cheng, Feng; Zhang, Rui-Jia; Fang, Ya; Wang, Zheng; Wu, Feng-Yao; Li, Pei-Zhang; Liang, Jun; Li, Rui; et al. (Frontiers in Endocrinology, 2021)
Background and Objective: Defects in the human sodium/iodide symporter (SLC5A5) gene have been reported to be one of the causes of congenital hypothyroidism (CH). We aimed to identify SLC5A5 mutations in Chinese patients with CH and evaluate the function of the mutation. Methods: Two hundred and seventy-three patients with primary CH were screened for mutations in SLC5A5 by next-generation sequencing. The expression and cellular localization of the novel compound heterozygous mutation in SLC5A5 were investigated. Functional activity of the mutants was further examined in vitro. Results: In 273 patients with CH, two novel pathogenic mutations p.G50fs and p.G421R in a compound heterozygous state in SLC5A5 was identified in a pediatric patient. G50fs was located in the first intercellular loop connecting transmembrane segment Ⅰ and Ⅱ, whereas G421R was in the TMS Ⅺ. In vitro experiments further showed that normal function of iodine transport of NIS mutants was markedly impaired. Conclusion: The undescribed compound heterozygous mutation of SLC5A5 was discovered in a Chinese CH patient. The mutation led to significantly reduced NIS expression and impaired iodide transport function accompanied by impaired the location of NIS on plasma membrane. Our study thus provides further insights into the roles of SLC5A5 in CH pathogenesis.